Response of small sharks to nonlinear internal waves. (22nd October 2019) - Pineda, Jesús; Rouse, Sally; Starczak, Victoria; Helfrich, Karl; Wiley, David
Abstract : Plankton and nekton may respond passively or actively to large‐amplitude, nonlinear internal waves (NLIW), with periods and wavelengths on the order of minutes and hundreds of meters, and the NLIW can cause direct or indirect changes in distribution. NLIW are ubiquitous in the coastal ocean, but understanding the influence of NLIW on organism response and distribution is challenging, because of NLIW unpredictability, short temporal and spatial scales, and the difficulty in resolving the biological response. Measurements of currents, temperature, and shark acoustic traces in Massachusetts Bay were used to evaluate the short‐term response of individuals as well as the mean effects on the distribution of an aggregation of small sharks, Squalus acanthias . In two NLIW events, we detected 527 and 3240 shark traces. Individuals moved up and down in response to the currents associated with the sinking and rising of the thermocline. However, mean distribution deepened during one of the events, suggesting that organisms did not merely move in concert with the thermocline oscillation, but that sharks instead might have responded actively. Measurements of vertical currents and shark's depth change during one of the NLIW events indicate that with downward currents (sinking of the thermocline), the sharks tend to react passively. However, in response to the fastest upward currents, sharks appeared to swim down, supporting an active response in the rising phase of the wave. NLIW and other high‐frequency processes can have a profound influence on the distribution of pelagic organisms, yet their ecological consequences remain largely unaccounted for.